(untitled) (Majalah Kedokteran Bandung, 2026)
Superficial wounds infected with Staphylococcus aureus trigger inflammatory responses and oxidative stress that impair wound healing. The secretome from hypoxia-conditioned mesenchymal stem cells (SH-MSC) has been shown to modulate inflammation by upregulating anti-inflammatory mediators, including IL-10 and STAT3. This study aimed to evaluate the effect of SH-MSC gel on IL-10 and STAT3 gene expression in superficial wounds infected with Staphylococcus aureus. This experimental study was conducted at the Stem Cell and Cancer Research (SCCR) Laboratory, Semarang, Indonesia from January to February 2024. A post-test control group design was used, with Wistar rats divided into five groups. Groups K2, K3, P1, and P2 consisted of Wistar rats with superficial wounds infected with Staphylococcus aureus, while K1 served as the healthy control. K2 was the negative control (treated with 100 mg of base gel), and K3 was the positive control (treated with topical gentamicin). In the experimental groups, P1 received 25% SH-MSC gel, while P2 was treated with 50% SH-MSC gel. The expression of IL-10 and STAT3 genes was analyzed using the Mann–Whitney test. The results showed a significant increase in IL-10 gene expression in P1 (p=0.048) and P2 (p<0.001) when compared with K2. The STAT3 gene expression was also significantly higher in P1 and P2 than in K3 (p<0.001). These findings indicate that SH-MSC gel upregulates IL-10 and STAT3 gene expression in Staphylococcus aureus-infected superficial wounds, suggesting an anti-inflammatory mechanism of action.